1998
DOI: 10.1016/s0304-3959(98)00019-0
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine-enhanced opiate analgesia in cancer patients requiring morphine dose escalation: a double-blind, placebo-controlled study

Abstract: The ability of nimodipine, a dihydropyridine calcium antagonist, to reduce the daily dose of oral morphine in cancer patients who had developed dose escalation, was tested in 54 patients under randomized, double-blind, placebo-controlled conditions. We selected patients that required at least two successive increments of morphine to maintain pain relief. A possible pharmacokinetic interaction between nimodipine and morphine was also studied in 14 patients by assaying steady-state serum levels of morphine and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…It is interesting to note that the tractus solitarius nucleus is among the areas where µ-opioid receptor down-regulation was not prevented by the association of nimodipine to the chronic sufentanil treatment. In agreement with this finding, opioid-induced respiratory depression was not potentiated by simultaneous treatment with nimodipine in rats (Ruiz et al 1993) or in humans (Santillán et al 1998).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is interesting to note that the tractus solitarius nucleus is among the areas where µ-opioid receptor down-regulation was not prevented by the association of nimodipine to the chronic sufentanil treatment. In agreement with this finding, opioid-induced respiratory depression was not potentiated by simultaneous treatment with nimodipine in rats (Ruiz et al 1993) or in humans (Santillán et al 1998).…”
Section: Discussionsupporting
confidence: 86%
“…In clinical studies, we have previously demonstrated that the calcium channel blocker nimodipine reversed morphine dose escalation during chronic pain treatment in cancer patients (Santillán et al 1994(Santillán et al , 1998. In rats, chronic and simultaneous treatment with sufentanil and nimodipine not only prevented the development of tolerance, but induced supersensitivity to the analgesic effect of the opioid (Dierssen et al 1990;Díaz et al 1995a).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Total oral daily dose of morphine was significantly reduced by nimodipine (120 mg/day) from 283 to 159 mg. Intrathecal morphine was also reduced. This data was confirmed by a randomized, double-blind, placebo-controlled study which was published 4 years later (Santillan et al, 1998). The study started with 54 cancer patients.…”
Section: L-type Vdcc Inhibitors In Combination With a U-opioid Agonistmentioning
confidence: 74%
“…The dose of morphine may be reduced with co-administration of dexamethasone or ketorolac or when it is combined intrathecally with bupivacaine or clonidine [9,14,134,195]. Nimodipine, a calcium channel blocker, enhances analgesia in cancer patients requiring regular dose increments of morphine to control pain [241]. These interactions are not pharmacokinetic but pharmacodynamic in nature [134,195].…”
Section: Drug Interactionsmentioning
confidence: 99%